Information Security Management of Smart Campus System Based on Big Data - Hongfei Xiao (Forest Chemicals Review, 1970)
Smart campus information security construction is an important part of information construction in higher vocational colleges. With the wide application of all kinds of information systems, the importance of information security is also getting more and more attention. At present, many problems in higher vocational colleges, such as imperfect information system construction and nonstandard programming of application system, may endanger the information security of intelligent campus in higher vocational colleges. In this paper, the current situation of information security construction in higher vocational colleges was analyzed and studied, and the management measures to strengthen the management and control of information security risks in smart campus were put forward in view of the shortcomings of information security construction in smart campus at present, so as to provide reference for information security management in smart campus in higher vocational colleges and escort smart campus.